A Review on GCL Performance in Geotechnical Engineering - Najafi, Fatemeh; Chegenizadeh, A; Nikraz, Hamid (Planetary Scientific Research Centre, 2012)
Over the past decade, geosynthetic clay liners (GCLs) have gained widespread popularity as a substitute for compacted clay liners in cover systems and composite bottom liners. They are also used as environmental protection barriers in transportation facilities or storage tanks, and as single liners for canals, ponds or surface impoundments. As a result, they are being investigated intensively, especially in regard to their hydraulic and diffusion characteristics, chemical compatibility, mechanical behaviour, durability and gas migration. In this paper, a review of the main findings is presented. From this work, a general insight is gained on outstanding effective factors on GCLs’ different performances and will additionally be used to develop GCL applications. An accurate interaction analysis of this system will be a remarkable contribution to the field as it will allow GCLs to be more effectively applied to a wider range of geotechnical issues.